Juridical and Sociological Foundations of Institutionalizing Sharia Economics in Indonesia - Suadi, Amran (Lex Publica, 2021)
Throughout the history of Islamic economics, economic freedom has been guaranteed by various traditions of society and by its legal system. In Indonesia, the concept of Islamic economics was born in the 1980s but was introduced to the public in 1991 when Bank Muamalat Indonesia was established, which was then followed by other financial institutions. Discussions on the future prospects of the Islamic economy in Indonesia should ideally begin by placing the legal basis as formal legality. Starting from Law No. 7 of 1992 concerning Banking, Government Regulation No. 72 of 1992 concerning Banks Based on Profit Sharing Principles, Law No. 10 of 1998 concerning Amendments to Law No. 7 of 1992 concerning Banking, then strengthened through Law No. 23 of 1999 concerning Bank Indonesia (BI), until the promulgation of Law No. 21 of 2008 concerning Sharia Banking, it seems very clear that the sharia economic system, especially in the banking system in Indonesia, already has legal legitimacy and legal certainty in a formal juridical manner. The sociological foundation of sharia economics in Indonesia can be seen from the community’s support and the development of sharia economics in Indonesia. The main reason that causes Islamic bank customers to become conventional bank customers still is rational reasons in the ease of financial transactions. They hope that the network of Islamic banks can be expanded and that Islamic banks can improve services and products that can accommodate their needs in financial transactions. Paying attention to this, in fact, the prospects for the Islamic economy are very promising in the future. From the description above, it can be understood that the future prospects of the Islamic economy in Indonesia are very bright and promising, both in the context of the juridical basis and in the context of its philosophical foundation. Abstrak Sepanjang sejarah ekonomi Islam, kebebasan ekonomi telah dijamin oleh berbagai tradisi masyarakat dan sistem hukumnya. Di Indonesia, konsep ekonomi Islam lahir pada tahun 1980-an namun diperkenalkan ke masyarakat pada tahun 1991 ketika Bank Muamalat Indonesia didirikan yang kemudian diikuti oleh lembaga keuangan lainnya. Pembahasan prospek ekonomi syariah di Indonesia ke depan idealnya dimulai dengan menempatkan landasan hukum sebagai legalitas formal. Berawal dari Undang-Undang No. 7 Tahun 1992 tentang Perbankan, Peraturan Pemerintah No. 72 Tahun 1992 tentang Bank Berdasarkan Prinsip Bagi Hasil, Undang-Undang No. 10 Tahun 1998 tentang Perubahan atas Undang-Undang No. 7 Tahun 1992 tentang Perbankan, kemudian diperkuat melalui Undang-Undang No. 23 Tahun 1999 tentang BI , sampai dengan diundangkannya Undang-Undang No. 21 Tahun 2008 tentang Perbankan Syariah, nampak sangat jelas bahwa sistem ekonomi syariah khususnya pada sistem perbankan di Indonesia sudah memiliki legitimasi hukum dan kepastian hukum secara yuridis formal. Landasan sosiologis ekonomi syariah di Indonesia dapat dilihat dari dukungan masyarakat dan perkembangan ekonomi syariah di Indonesia. Alasan utama yang menyebabkan nasabah bank syariah masih menjadi nasabah bank konvensional adalah karena alasan rasional dalam kemudahan transaksi keuangan. Mereka sangat berharap agar jaringan bank syariah dapat diperluas dan bank syariah dapat meningkatkan layanan dan produk yang dapat mengakomodir kebutuhan mereka dalam bertransaksi keuangan. Mencermati hal tersebut, sebenarnya prospek ekonomi syariah sangat menjanjikan di masa depan. Dari uraian di atas dapat dipahami bahwa prospek ekonomi syariah di Indonesia ke depan sangat cerah dan menjanjikan, baik dalam konteks landasan yuridis maupun konteks landasan filosofisnya. Kata kunci: Pendaftaran Hipotek, Mekanisme, Perlindungan Hukum, Sharia Economics